Analisis semiotika pada IGTV “Korupsi di tengah pandemi, jahat” - Rahmawanti, Annisa Nur (Universitas Lampung, 2024)
In the midst of the Covid-19 pandemic that has hit almost the entire world, including Indonesia, conditions are abnormal but different from the habit of corruption which is still carried out by officials who no longer have morals as trustworthy leaders of the people. Through the “Narasi” Najwa Shihab’s IGTV, the event was packaged attractively so that it was presented briefly while it still referred to the hearts and aspiration of the people. This study used a qualitative research method with a semiotic analysis of Roland Barthes' model with denotation, connotation, and myth meanings. The object analyzed was the “Narasi IGTV” on Najwa Shihab’s Instagram. Based on the results of research by using Roland Barthes' semiotic analysis, it indicated that Najwa Shihab used many choices of words that indicated the crime term which had its own meaning in the video. In addition, through the “Narasi IGTV”, it affirmed the people's anger at officials who commited corruption.Keywords: Najwa Shihab, Semiotics, Online media